2019
DOI: 10.1002/ange.201911097
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Open Coordination Cage from Nonsymmetrical Imidazole–Pyridine Ditopic Ligands for Turn‐On/Off Anion Binding

Abstract: This work demonstrates an ew nonconventional ligand design, imidazole/pyridine-based nonsymmetrical ditopic ligands (1 and 1 S ), to construct ad ynamic open coordination cage from nonsymmetrical building blocks.Upon complex formation with Pd 2+ at a1 :4 molar ratio, 1 and 1 S initially form mononuclear PdL 4 complexes (Pd 2+ (1) 4 and Pd 2+ (1 S ) 4 )w ithout formation of ac age.T he PdL 4 complexes undergo astoichiometrically controlled structural transition to Pd 2 L 4 open cages ((Pd 2+ ) 2 (1) 4 and (Pd 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…45 Perhaps unsurprisingly, in each of these 12 instances, the cis-Pd 2 L 4 isomer was predicted to be the favoured structure, again in agreement with previous work. 45,47,48 Indeed, for most of the ligands (51 of 60; 85 %), the cis cage isomer was found to be the most stable (…”
Section: Ranking Ligands By Their Cage Isomer Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…45 Perhaps unsurprisingly, in each of these 12 instances, the cis-Pd 2 L 4 isomer was predicted to be the favoured structure, again in agreement with previous work. 45,47,48 Indeed, for most of the ligands (51 of 60; 85 %), the cis cage isomer was found to be the most stable (…”
Section: Ranking Ligands By Their Cage Isomer Propertiesmentioning
confidence: 99%
“…Density functional theory (DFT) calculations have been previously used to rationalise experimentally observed self-sorting in low symmetry metallo-supramolecular systems by exploring the relative energies of the potential configurational isomers. 41,43,45,47,48 Indeed, in recent work, we found that the formation of a single Pd 2 L 4 cage isomer from the selfassembly of unsymmetrical ditopic ligands with Pd(II) ions only occurred when there was a significant difference in the calculated energies (on the order of at least 5 kJ mol −1 ) of the possible isomers. 45 As such, we envisaged that a high-throughput computational workflow could be used to rapidly explore the chemical space of low symmetry MOPs and aid in their design and minimise trial-and-error experimental efforts.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…43 Crowley and co-workers recently reported a [PdPtL 4 ] cage in which the different labilities of the two metal ions allowed selective sequestration of the Pd(II) ions to open the cage without complete dissociation of the ligands. 44 We 45,46 and others [47][48][49][50] have recently begun to explore an alternative approach that uses unsymmetrical ligands to access lower symmetry structures. 51 The lack of bilateral symmetry introduced into the ligand structure means four possible isomers of the resultant dipalladium cage can form (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The binding properties of coordination cages in solution [5][6][7][8][9][10][11][12][13][14][15][16][17] has been tailored to species ranging from gases [18][19][20][21] to heavy metals 21 , and neutral [22][23][24] and charged compounds [25][26][27][28][29][30] . A cage dissolved in one fluid phase is capable of extracting a guest from another immiscible one, without crossing the phase barrier 31 .…”
mentioning
confidence: 99%